Keberadaan Serangga Malam Berdasarkan Efek Warna Lampu Di Kebun Raya Liwa - Faradila, Annisa; Nukmal, Nismah; Pratami, Gina Dania; Tugiyono, T (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Insects are invertebrate animals with diversity and have a high adaptability. Insects have properties that are very sensitive to light, especially night insects. Night insect species in the Liwa Botanical Garden (KRL) have not been identified. This research was conducted from October to November 2019 in the Liwa Botanical Garden, West Lampung Regency. The purpose of this study was to determine the effect of the color of the lights (red, yellow, blue and white) on the presence of night insects on KRL. This research was conducted using the Purposive Sampling method using red, yellow, blue and white light. The insects that were caught were identified in the Zoology Laboratory of the Faculty of Mathematics and Natural Sciences Unila and analyzed descriptively based on morphological similarities with the book Borror et al., (1992). The data obtained were analyzed using the ANOVA test using Minitab 19. The results of this study showed that in the Araceae area of the Taman Liwa Botanical Garden the blue light traps caught a maximum of 457 night insects while the red light traps caught the night insects with the least number 19 tail. This study also showed that light intensity correlated with the number of night insects obtained.